Oxidative modification and gradient acid precipitation fractionation of lignin in deep eutectic solvent with reversibly-soluble base - Dayu Sun; Huijun Liu; Xiaoshi Lei; Hongwei Wu; Zhixiu Yang; Lijing Gao; Wei Xu; Ruiping Wei; Xiaomei Pan; Guomin Xiao (Journal of Environmental Chemical Engineering, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

Emodin alleviates renal fibrosis by targeting the ALKBH1/m5C axis to sustain TRPV4 expression and inhibit TGF-β1/Smad2/3 signaling - Yan Liu; Xi Sun; Wansen Sun; Ruiping Li (Toxicology and Applied Pharmacology, 2026)

Microplastic distribution and occurrence in benthic species along river–sea continua: Implications for coastal aquaculture in the South Yellow Sea - Xiaoping Sun; Ruiping Yang; Jing Ji; Jason C. White; Yu Shen (Estuarine, Coastal and Shelf Science, 2026)

Conversion of waste activated sludge into high-quality denitrification carbon source via moderate pretreatment: Performance, mechanisms, and environmental benefits evaluation - Yifan Sun; Ge Song; Shunan Zhao; Fangzhou Wang; Kai Zhao; Wenwei Li; Ruiping Liu (Resources, Conservation and Recycling, 2026)

TGEV infection activates pro‑inflammatory signaling via the YY1/HSP40/NF‑κB pathway in intestinal epithelial cells and organoids - Shuai Gao; Zhe Chao; Zongxi Cao; Feng Wang; Ruiping Sun; Guangliang Liu (Veterinary Microbiology, 2026)

Moderate warming enhances CO2 concentrating mechanisms in diatoms by increasing CO2: HCO3− uptake ratio - Xuexia Bai; Jia-Zhen Sun; Wanjuan Song; Bixin Zhang; Xin Lin; Bangqin Huang; Ruiping Huang; Kunshan Gao (Algal Research, 2026)

Analyzing the nitrogen transformation mechanisms in anaerobic digestion of sewage sludge enhanced by thermal hydrolysis pretreatment - Ruiyi Xie; Dan Xu; Shuai Ma; Manman Cao; Junhong Li; Na Xiao; Ke Sun; Ruiping Liu; Fei Wang (Process Safety and Environmental Protection, 2026)

Biomimetic polydopamine-intercalated MgAl-layered double hydroxide for effective skin photoprotection and photodamage recovery - Pengqi Zhu; Xichen Sun; Ye Cai; Mingchen Zhao; Ruiping Zhang; Jinghua Sun (Journal of Photochemistry and Photobiology B: Biology, 2026)

Green oxidation of corn stover lignin as reinforcing plasticizer and UV-blocking agent for polyvinyl alcohol composites: process optimization and techno-economic analysis - Dayu Sun; Hongwei Wu; Zhixiu Yang; Lijing Gao; Tang Tang; Wei Xu; Ruiping Wei; Xiaomei Pan; Guomin Xiao (Bioresource Technology, 2026)

Sustainable risk management of heavy metal contaminated agricultural soil: Current frameworks and future perspectives - Bin Zhao; Hao Zhang; Jan Mulder; Xueting Sun; Gudny Okkenhaug; Yuanliang Jin; Weisheng Chen; Ruiping Liu; Liping Fang; Fangbai Li (Journal of Environmental Management, 2025)

Macrofaunal biodiversity and trophic structure varied in response to changing environmental properties along the Spartina alterniflora invasion stages - Li Yang; Rui Pan; Shuang Wang; Zhangyan Zhu; Hongshan Li; Ruiping Yang; Xiaoping Sun; Baoming Ge (Marine Pollution Bulletin, 2025)

Strategies optimization to improve environmental benefit of chicken manure anaerobic digestion in China: Insight from life cycle assessment - Fangzhou Wang; Shunan Zhao; Yizhu Sun; Ge Song; Yifan Sun; Kai Zhao; Ruiping Liu; Yu-You Li (Journal of Cleaner Production, 2025)

Circ_0049979 ameliorates myocardial infarction through improving Cx43-mediated endothelial functions - Meng Sun; Shaodong Zhai; Yangyang Gao; Nan Hu; Rui Wang; Ruiping Zhang (Toxicology and Applied Pharmacology, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Corrigendum to “Spatially resolved metabolomics combined with multicellular tumor spheroids to discover cancer tissue relevant metabolic signatures” [Anal. Chim. Acta 1155 (2021) 338342] - Qingce Zang; Chenglong Sun; Xiaoping Chu; Limei Li; Wenqiang Gan; Zitong Zhao; Yongmei Song; Jiuming He; Ruiping Zhang; Zeper Abliz (Analytica Chimica Acta, 2024)

Biocatalytic Au10 clusters for sepsis management via modulation of systemic inflammation - Qi Xin; Sufei Zhou; Lijie Zhang; Si Sun; Di Liu; Hao Wang; Xiaoyu Mu; Xiaoxing Fang; Qi Chen; Huanhuan Qiao; Xiao-Dong Zhang; Ruiping Zhang (Chemical Engineering Journal, 2024)

An evaluation of microplastic contamination in the marine waters and species in the coastal region of the South Yellow Sea, China - Xiaoping Sun; Ruiping Yang; Jing Ji; Zebin Zhu; Jason C. White; Yu Shen (Journal of Hazardous Materials, 2024)

Linking the potential activities of methanogens and methanotrophs to their communities under different fertilization regimes in coastal saline paddy soils - Xianglin Dai; Jianping Sun; Zijing Zhao; Ruiping Ma; Zhenyu Zheng; Yahui Liu; Xiubin Wang; Wei Zhou (Applied Soil Ecology, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Multichannel electron transmission and multiple light scattering in CoCo PBA/CoSn(OH)6/Pt photocatalyst for effective conversion of simulated flue gas - Wenting Wu; Yuanfeng Wu; Zongqi Zhang; Lipeng Sun; Ruiping Wei; Jin Zhang; Lijing Gao; Xiaomei Pan; Jin Yu; Guomin Xiao (Fuel, 2023)

Interactive effects of high temperature and crude protein levels on growth performance, nitrogen excretion, and fecal characteristics of broilers - Quanwei Liu; Jinghai Feng; Limin Wei; Chengjun Hu; Xinli Zheng; Ruiping Sun; Minhong Zhang (Tropical Animal Health and Production, 2022)

Plant miR167e-5p promotes 3T3-L1 adipocyte adipogenesis by targeting β-catenin - Ting Chen; Fei Ma; Yongjia Peng; Ruiping Sun; Qianyun Xi; Jiajie Sun; Jin Zhang; Yongliang Zhang; Meng Li (In Vitro Cellular & Developmental Biology - Animal, 2022)

Human umbilical cord mesenchymal stem cells ameliorate depression by regulating Jmjd3 and microglia polarization in myocardial infarction mice - Youyang Zhang; Xinan Wang; Yuhang Li; Ruiping Liu; Jiangqi Pan; Xiane Tang; Shuifen Sun; Jie Liu; Wenlin Ma (Psychopharmacology, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Physiological and molecular responses to ocean acidification among strains of a model diatom - Ruiping Huang; Jiancheng Ding; Jiazhen Sun; Yang Tian; Chris Bowler; Xin Lin; Kunshan Gao (Limnology and Oceanography, 2020)
Differential responses of diatoms, an important group of marine primary producers to ocean acidification, have been well documented. However, studies so far are based on limited representative strains from key species. Investigation of strain level responses will help us better understand the contrasting discrepancy in diatom responses to ocean acidification. Here, we selected four strains of the model diatom Phaeodactylum tricornutum isolated from different regions of the global ocean, representing all genotypes based on internal transcribed spacer 2 sequences, and investigated strain‐specific responses to ocean acidification. In response to ocean acidification, changes in carbon metabolism varied among strains, although no significant effects of ocean acidification on growth rates or pigments were observed in any strains. The expression of genes encoding plasma membrane bicarbonate transporters was downregulated in strain Pt4, reflecting a potential decrease in active uptake, which was not observed in the other strains. Reduction of CO 2 concentrating mechanism efficiency was also indicated by the regulated expression of genes encoding carbonic anhydrases that catalyze the interconversion of and CO 2 in the pyrenoids and pyrenoid‐penetrating thylakoid, which exhibited different patterns among the strains. Under ocean acidification conditions, C4‐like metabolism appeared to redistribute carbon flux to gluconeogenesis in strain Pt1, and lipid synthesis in strains Pt8 and Pt11, rather than participating in net photosynthetic carbon fixation. These variations were incompletely correlated with phylogenetic relationship in different strains, implying that the habitat‐adapted imprints of the different strains could also be responsible for their differential responses to ocean acidification.

Genome of Bacillus sp. strain QHF158 provides insights into its parasporal inclusions encoded by the S-layer gene - Yinghong Jin; Junhui Wang; Qian Liu; Haifang Qiu; Yangyang Wang; Jiayi Zhou; Jie Sun; Peng Li; Ruiping Wang; Wenfei Zhang (Brazilian Journal of Microbiology, 2020)

Human leukocyte antigen (HLA)-C polymorphisms are associated with a decreased risk of rheumatoid arthritis - Yiqun Zhang; Hui Zhang; Yong Huang; Rongbin Sun; Ruiping Liu; Jie Wei (Molecular Biology Reports, 2014)

MMP-2, TNF-α and NLRP1 polymorphisms in Chinese patients with ankylosing spondylitis and rheumatoid arthritis - Rongbin Sun; Yong Huang; Hui Zhang; Ruiping Liu (Molecular Biology Reports, 2013)

Facilitated legume nodulation, phosphate uptake and nitrogen transfer by arbuscular inoculation in an upland rice and mung bean intercropping system - Yuefeng Li; Wei Ran; Ruiping Zhang; Shubin Sun; Guohua Xu (Plant and Soil, 2009)